2010
DOI: 10.5037/jomr.2029-283x.2010.1.1.e5
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tube Potential on Periodontal Bone Level Measurements and Subjective Image Quality Using a Digital Photostimulable Storage Phosphor Sensor

Abstract: Objectives:The purpose of the present study was to determine the measurement accuracy and subjective image quality for periodontal disease diagnosis when using two X-ray tube voltages with a digital photostimulable storage phosphor sensor. Material and Methods: A digital photostimulable storage phosphor (PSP) sensor (Vistascan) and a multipulse X-ray generator (Prostyle Intra) with two tube voltages were used in this study. The front, premolar and molar region of two adult human cadaver skulls jaws were imaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In a later study using a digital sensor technique [13] no significant difference was found in the diagnostic accuracy of approximal carious lesions when using tube voltages of 60 kV and 70 kV. In another previous study by Vandenberge and Jacobs [15] it was concluded that 63 kV and 70 kV provided a similar diagnostic accuracy and image quality for periodontal disease. The main opinion among vendors and many users is that digital sensors often perform with a higher subjective image quality at a higher tube voltage, although no studies could be found supporting this belief.…”
Section: Introductionmentioning
confidence: 97%
“…In a later study using a digital sensor technique [13] no significant difference was found in the diagnostic accuracy of approximal carious lesions when using tube voltages of 60 kV and 70 kV. In another previous study by Vandenberge and Jacobs [15] it was concluded that 63 kV and 70 kV provided a similar diagnostic accuracy and image quality for periodontal disease. The main opinion among vendors and many users is that digital sensors often perform with a higher subjective image quality at a higher tube voltage, although no studies could be found supporting this belief.…”
Section: Introductionmentioning
confidence: 97%